Caste and tobacco use: Decomposing inequalities using Global Adult Tobacco Survey, India - Lucky Singh; Prashant Kumar Singh; Shashi Kala Saroj; Ritam Dubey; Shalini Singh (PLoS ONE, 2026)
Background India ranks second globally in tobacco consumption, with marked disparities across socially stratified caste groups. Despite tobacco control efforts, Scheduled Tribes (ST) and Scheduled Castes (SC)—historically marginalized communities—exhibit elevated tobacco use. This study examines caste-based disparities in smoked and smokeless tobacco (SLT) use and identifies factors contributing to these inequalities. Methods We analyzed nationally representative data from the Global Adult Tobacco Survey (GATS) 2016−17, comprising 74,037 adults aged ≥15 years. Social groups were classified as ST, SC, Other Backward Classes (OBC), and General categories. We estimated prevalence rates, used multivariable logistic regression to assess associations with socio-demographic factors, and employed multivariate decomposition analysis to quantify contributors to inter-group disparities. Results Overall tobacco use prevalence was 28.6%, with substantial variation: ST (36.0%), SC (28.9%), OBC (29.1%), and General (23.1%). SLT use was particularly high among ST (27.7%) and SC (20.7%) compared to General (16.0%). Men had 16-fold higher odds of SLT use (AOR: 16.4; 95%CI:15.2-17.7) and 23-fold higher odds of smoking [Adjusted Odds Ratio (AOR): 23.1; 95%CI:20.8-25.6] compared to women, with similar patterns within each social group. Lower education, older age, disrupted marriage, rural residence, and poor wealth status were independently associated with higher tobacco use. Decomposition analyses revealed that sex (38%), education (24%), and region (18%) explained most between-group differences, with substantial tobacco use concentrated in Eastern, Central, and Northeastern states. Conclusions Pronounced caste-based tobacco use disparities persist in India, disproportionately affecting socioeconomically disadvantaged ST and SC populations, particularly older, less-educated in rural areas. Achieving Sustainable Development Goal 3.a requires targeted interventions addressing these structural inequalities through culturally appropriate cessation programs, enhanced health education, and region-specific tobacco control policies.